Deletions in cox2 mRNA result in loss of splicing and RNA editing and gain of novel RNA editing sites. - Stefanie Grüttner (Public Library of Science (PLoS), 2013)
As previously demonstrated, the maize cox2 RNA is fully edited in cauliflower mitochondria. Use of constructs with a deleted cox2 intron, however, led to a loss of RNA editing at almost all editing sites, with only a few sites still partially edited. Likewise, one deletion in exon 1 and three in exon 2 abolish RNA editing at all cox2 sites analyzed. Furthermore, intron splicing is abolished using these deletions. Mutation of a cytosine residue, which is normally edited and localized directly adjacent to the intron, to thymidine did not result in restoration of splicing, indicating that the loss of splicing was not due to loss of RNA editing. One deletion in exon 2 did not lead to loss of splicing. Instead, most editing sites were found to be edited, only three were not edited. Unexpectedly, we observed additional RNA editing events at new sites. Thus it appears that deletions in the cox2 RNA sequence can have a strong effect on RNA processing, leading to loss of splicing, loss of editing at all sites, or even to a gain of new editing sites. As these effects are not limited to the vicinity of the respective deletions, but appear to be widespread or even affect all editing sites, they may not be explained by the loss of PPR binding sites. Instead, it appears that several parts of the cox2 transcript are required for proper RNA processing. This indicates the roles of the RNA sequence and structural elements in the recognition of the editing sites.